2016
DOI: 10.1002/jib.381
|View full text |Cite
|
Sign up to set email alerts
|

Review: Pure non‐Saccharomycesstarter cultures for beer fermentation with a focus on secondary metabolites and practical applications

Abstract: Recently there has been increased interest in using non‐Saccharomyces yeasts to ferment beer. The worldwide growth of craft beer and microbreweries has revitalised the use of different yeast strains with a pronounced impact on aroma and flavour. Using non‐conventional yeast gives brewers a unique selling point to differentiate themselves. Belgian brewers have been very successful in using wild yeasts and mixed fermentations that often contain non‐Saccharomyces yeasts. Historically, ancient beers and beers prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 93 publications
(260 reference statements)
1
76
0
16
Order By: Relevance
“…These compounds are desirable; if present in moderate levels, they help increase the flavor complexity of beers, whereas high amounts affect negatively beverage aroma, conferring undesirable, solvent-like buttery and medicinal notes [30]. Otherwise, most authors reported very low quantities of isoamyl acetate, which could be explained by the ability of B. bruxellensis to break down this aroma compound, which is highly desirable in wheat beer [31].…”
Section: Non-conventional Yeasts For Bioflavoringmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds are desirable; if present in moderate levels, they help increase the flavor complexity of beers, whereas high amounts affect negatively beverage aroma, conferring undesirable, solvent-like buttery and medicinal notes [30]. Otherwise, most authors reported very low quantities of isoamyl acetate, which could be explained by the ability of B. bruxellensis to break down this aroma compound, which is highly desirable in wheat beer [31].…”
Section: Non-conventional Yeasts For Bioflavoringmentioning
confidence: 99%
“…Torulaspora delbrueckii, a common contaminant in the brewing environment and suggested as a potential brewing yeast firstly by King and Dickinson [36], has been shown to be able to produce high levels of amyl alcohol (fruity flavours) [31] and is often associated with wheat beer, a style typically associated with pronounced fruit notes. This yeast species has the additional advantage of being resistant to the various stresses encountered during brewing, although different strains exhibited different abilities to ferment wort sugars, and this characteristic may explain the variable performance observed in different studies [31,37,38].…”
Section: Non-conventional Yeasts For Bioflavoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The altered yeast metabolism during high-gravity fermentation not only changes the quality of the finished beer but also the material composition of the yeast [10,18]. In addition, the biodiversity of the generated spent yeast in breweries is increased through the use of various alternative non-Saccharomyces strains as pure starter cultures for beer production [19,20]. Improper storage or handling of the spent yeast can result in contamination with various microorganisms, which can impact the subsequent yeast extract production process [21].…”
mentioning
confidence: 99%
“…This is the most important group of secondary metabolites essential for aromatic characteristics as they impart a fruity and sweet note to alcoholic beverages during fermentation. Esters are divided into acetate esters (synthesized from a higher alcohol or ethanol with acetic acid) and medium-chain fatty acid ethyl esters (made from a medium-chain fatty acid and an ethanol radical) [111,112].…”
Section: Chemical Products Of Fermentationmentioning
confidence: 99%